2021
DOI: 10.3390/foods10030517
|View full text |Cite
|
Sign up to set email alerts
|

Active Packaging-Releasing System with Foeniculum vulgare Essential Oil for the Quality Preservation of Ready-to-Cook (RTC) Globe Artichoke Slices

Abstract: Two globe artichoke genotypes, “Spinoso sardo” and “Opera F1”, have been processed as ready-to-cook (RTC) slices and refrigerated at 4 °C for 12 days (i) to evaluate the suitability to be processed as RTC slices; (ii) to evaluate the effect of a Foeniculum vulgare essential oil (EO) emitter, within an active package system, to delay quality decay, thus extending shelf life; (iii) to estimate the impact of EO emitter on the sensory profile of the RTC slices after cooking. Results revealed that both globe artich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
4
3
1
Order By: Relevance
“…After 9 days of storage at 2 • C, Cys + 75 EOs and Cys + 150 EOs treated artichokes presented an 18.73 (19.41 ± 0.47%) and 20% (19.72 ± 0.75%) reduction of WL compared to the non-treated artichokes (24.26 ± 1.61%), respectively. In previous studies, the use of Foeniculum vulgare EOs on its own or in combination with cysteine observed a similar WL when artichokes were hermetically packed in PET trays [44,51]. In the present study, a decrease in the WL has been observed, probably due to the absence of packaging.…”
Section: Effect Of the Application Of Cysteine And Eos On Quality Par...supporting
confidence: 77%
See 3 more Smart Citations
“…After 9 days of storage at 2 • C, Cys + 75 EOs and Cys + 150 EOs treated artichokes presented an 18.73 (19.41 ± 0.47%) and 20% (19.72 ± 0.75%) reduction of WL compared to the non-treated artichokes (24.26 ± 1.61%), respectively. In previous studies, the use of Foeniculum vulgare EOs on its own or in combination with cysteine observed a similar WL when artichokes were hermetically packed in PET trays [44,51]. In the present study, a decrease in the WL has been observed, probably due to the absence of packaging.…”
Section: Effect Of the Application Of Cysteine And Eos On Quality Par...supporting
confidence: 77%
“…Furthermore, in a previous study, 'Blanca de Tudela' freshcut artichokes were treated with different concentrations of cysteine (10-50 mol/m 3 ) and packed in polypropylene films, achieving L* values of 60.17 ± 0.22 after 4 days at 5 • C [29], while in the present study, the combination with EOs resulted in a 28% higher lightness. A decrease in L* with storage time was observed in all treatments and has been previously reported [44,51]. It is associated with the PPO enzymatic reaction that occurs during the browning process [52,53].…”
Section: Effect Of the Application Of Cysteine And Eos On Artichoke B...supporting
confidence: 76%
See 2 more Smart Citations
“…In general, tertiary heads showed the worst aptitude to developed fresh-cut artichoke product related to a high browning on the artichoke head (Figure 3). PPO activity is the key enzyme involved in the enzymatic browning process, which generates dark pigments called melanoidins, and are unacceptable in terms of safety as they could support microbial growth [44]. Several studies have showed that the browning process might be prevented by chemical and physical methods to inhibit PPO enzyme activity, including the reduction of temperature and/or oxygen concentration, the use of modified atmosphere packaging (MAP), and the application of anti-browning agents, coatings, and innovative packaging [3,29,[45][46][47][48].…”
Section: Evaluation Of Artichoke Browning For Different Artichoke Hea...mentioning
confidence: 99%